Pengaruh Perceived Ease of Use dan Perceived Usefulness terhadap Keputusan Penggunaan Aplikasi Tokopedia melalui Trust sebagai Variabel Intervening - Sito Putri, Rizky Ramadhany; Iriani, Sri Setyo (Jurnal Ilmu Manajemen, 2021)
The development of technology-based businesses has increased as a result of the Covid-19 pandemic. One of them is e-commerce as an online shopping service provider. The purpose of this study is to analyze and discuss the effect of perceived ease of use, perceived usefulness, and trust in actual system use decisions. Respondents in this study were people aged 15–39 who had used the Tokopedia application in 2020 and accessed it via smartphone. The sample used was 200 respondents. The sampling method using non-probability sampling, and the sampling technique is judgemental sampling. The data collection techniques using an online questionnaire and analyzed using Path Analysis in AMOS program 23 version. This study found that perceived ease of use has a positive and significant effect on trust and actual system use. Perceived usefulness has a positive and significant effect on trust but does not affect actual system use. Moreover, trust has a positive and significant effect on actual system use. Furthermore, the result was found that perceived ease of use and usefulness positively affect actual system use with trust a mediating variable. Based on these result, it is recommended that Tokopedia could improve the easiness and the usefulness of their application system while keep maintaining the trust of its users.